INTEGRATION OF EUROPEAN VALUES INTO EDUCATION, SCIENCE AND SPOR TS: UKRAINIAN DIMENSION THROUGH THE PRISM OF THE EVUESS PROJECT. - Galan, Iaroslav (My University, 2025)
The article analyzes the mechanisms for implementing European values in the Ukrainian edu-cational, scientific, and sports space, as well as the types of impact of the implemented project (EVUESS). The results of a sociological survey are presented, revealing an insufficient awareness of the target groups about the values of the European Union. In order to disseminate the project results, various activities are being carried out to promote EU values in Ukraine, particularly through participation in thematic lectures, discussions, conferences, and winter and summer schools. Such activities are essential for shaping values and raising European consciousness among young people. The topic's relevance is driven by the need to strengthen the democratic potential of Ukrainian society in the face of current challenges and threats.
Keywords: European values; integration; education; science; sports; EVUESS